Linguistic Political Prognostics: Models and Scenarios of Future (Journal of Pedagogical Inventions and Practices, 2022)
The present paper briefly recalls theoretical preconditions for forming a new approach – linguistic political prognostics. The authors review theories and methods used for strengthening a future focus in political discourses and work out two main tools – a model of future and a scenario of future